Gambaran histopatologi penyembuhkan luka pencabutan gigi pada makrofag dan neovaskular dengan pemberian getah batang pisang ambon - Hendrik Setia Budi; Pratiwi Soesilowati; Zhafirah Imanina (Faculty of Dentistry, Universitas Gadjah Mada, 2017)
Tooth extraction healing on macrophages and neovascular histopathology induced by ambonese banana stem sap gel. Blood clotting is very important in the early wound healing process. Blood clots will soon be filled with a connective tissue due to the induction of growth factors as granulation tissue. The expression of platelet derived growth factors (PDGF)-BB using the Ambonese banana stem sap gel (Musa paradisiaca var. sapientum) can increase the proliferation of fibroblasts. Macrophages and neovascular support in the early phase of healing. The purpose of this research was to demonstrate that Ambonese banana stem sap gel (GEGPA) can improve the macrophages and neovascular in the socket wound healing. Thirty six wistar rats were used and divided into 3 groups. The mandibular left incisor was extracted. The first group as control was given HPMC 4% gel on socket, the second group was given GEGPA 60%, and third group was given gelatin sponge. Rats were sacrificed on day 3 and 5 for histopathology examination of neovaskular and macrophages on the socket. The results showed that there was significantly different in the control group on a number of neovascular and macrophages in socket on day 3 (p<0.05). No significant difference on day 5 in all groups of neovascular and macrophages number (p>0.05). It was concluded that the use of GEGPA 60% acceleratedthe wound healing of tooth extraction socket by means of macrophages and neovascular increasing.ABSTRAKPembekuan darah sangat penting pada proses awal penyembuhan luka. Bekuan darah akan segera diisi oleh jaringan granulasi yang berasal dari induksi faktor pertumbuhan. Ekspresi platelet derived growth factors (PDGF)-BB yang diinduksi oleh pemberian gel ekstrak getah batang pisang ambon (Musa paradisiaca var. sapientum) dapat menunjukkan terjadinya peningkatan proliferasi fibroblas. Makrofag dan neovaskular sangat menunjang fase awal penyembuhan. Tujuan penelitian ini untuk membuktikan bahwa pemberian gel ekstrak getah batang pisang ambon (GEGPA) dapat meningkatkan jumlah makrofag dan neovaskular pada penyembuhan luka soket. Tikus strain Wistar sebanyak 36 ekor digunakan pada penelitian ini yang terbagi menjadi 3 kelompok. Semua tikus dilakukan pencabutan gigi pada insisive kirimandibula. Kelompok pertama sebagai kontrol, pada soket diberi gel hidroksipropil metil selulosa (HPMC) 4%, kelompok kedua diberi GEGPA 60%, dan kelompok ketiga diberi gelatin sponge. Tikus dikorbankan pada hari ke-3 dan 5 untuk pemeriksaan histopatologi neovaskular dan makrofag pada soket. Hasil penelitian menunjukkan terdapat perbedaan yang bermakna terhadap kelompok kontrol pada jumlah neovaskular dan makrofag soket pada hari ke-3 (p<0,05). Tidak ditemukan perbedaan yang bermakna pada jumlah neovaskular dan makrofag hari ke-5 (p>0,05). Disimpulkan bahwa pemberian GEGPA 60% dapat mempercepat penyembukan luka pencabutan gigi melalui peningkatan jumlah makrofag dan neovaskular.